AB0023 Combination of Igg N-Glycomics and Corresponding Transcriptomics Data to Identify Anti-Tnf-Alpha Treatment Responders in Rheumatoid Arthritis and Inflammatory Bowel Disease. (9th June 2015) - Váradi, C.; Guttman, A.; Hollό, Z.; Poliska, S.; Nagy, L.; Szekanecz, Z.; Váncsa, A.; Palatka, K.
Abstract : Background: Prediction of responsiveness in biological therapies is an important and challenging issue in different diseases. Analyzing glycosylation pattern changes of key serum glycoproteins is one of the possible avenues to follow disease remission. Objectives: The aim of this study was to investigate the changes of serum IgG glycoforms in rheumatoid arthritis (RA) and Crohn's disease (CD) patients in response to anti-tumor necrosis factor alpha (TNFα) treatment. Methods: IgG was isolated from patient serum samples using Protein A affinity pull-down, followed by the release of N-glycans with peptide-N-glycanase F. The released glycans were fluorescently tagged with aminopyrene-trisulfonate and analyzed by capillary gel electrophoresis with laser induced fluorescent detection. Results: Significant alterations were detected between responders and non-responders in both disease groups. In RA, three low abundant galactosylated structures were found to be significantly different before the treatment where in all of the cases responders showed higher galactosylation level. Unfortunately, no significant alteration was detected in RA in response to the treatment. In CD significant differences were detected in galactosylation level between responders and non-responders before the treatment (higher in the responder group). FA2G2S1 level was significantly increased in response to anti-TNFα therapy, thus being a possible candidate marker for responder identification. Interestingly, the level of this structure was not significantly altered in any of the RA groups suggesting disease specificity for CD. Conclusions: IgG N-glycomics and corresponding transcriptomics may be useful to reveal disease-specific alterations when assessing responses to anti-TNFα therapy in chronic inflammatory diseasaes, such as RA or CD. Disclosure of Interest: None declared